Beach profile data for the Elwha River Delta, 2011-11-23 - Miller, Ian (In: Miller, I (2019): Beach Profile Data for the Elwha River Delta, 2011-2018 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.901486, 2019)
Data were collected using GNSS survey methods, with a differential GPS operating in Real Time Kinematic (RTK) mode. Data from prior to 2013 were typically collected with a Magellan ProMark 3 traditional RKT-DGPS system (i.e. local base station and rover), with the base station sited on survey control markers installed in 1996, with survey control coordinates referenced to NAD83(CORS91). Starting in 2013 survey data were typically collected with an AshTech ProMark 200 RTK-DGPS system connected to the Washington State Reference Network. Survey data collected between January and November 2013 are referenced to NAD83(CORS96), and after November 2013 to NAD83(2011). Vertical data for surveys in 2012 and 2013 are referenced to NAVD88, presumably using Geoid96 (the survey control documentation does not specific a geoid). For all subsequent surveys the vertical data are referenced to NAVD88(Geoid09). No conversion were applied to these data to account for variations in horizontal or vertical coordinate system adjustments through time, but an error analysis suggests a standard deviation for the elevation data of between 0.03 and 0.05 m across the entire sampling period (2011-2018). All survey data were collected with the GNSS system mounted on a 2.05 m rover pole, held level as a transect line was traced in a cross-shore orientation on the beach. The associated text files include the horizontal (HRMS) and vertical (VRMS) root-mean-square errors estimated by the GNSS system, as well as the RTK-DGPS status reported by the GNSS system at the time each point was collected. Times are referenced to local Pacific time (either PST or PDT).
Keywords: Beach Nourishment; Elwha; Shoreline Change